2018
DOI: 10.2147/ijn.s182197
|View full text |Cite
|
Sign up to set email alerts
|

pH-triggered charge-reversal and redox-sensitive drug release polymer micelles co-deliver doxorubicin and triptolide for prostate tumor therapy

Abstract: AimTo significantly promote cancer cell uptake and to achieve combination therapy and on-demand drug release, a pH-triggered charge-switchable and redox-responsive drug-release nanovehicle was developed in this study.Materials and methodsThe nanocarrier was constructed by conjugating 3,3′-dithiodipropionic acid-modified doxorubicin (DTPA-DOX) and 2,3-dimethylmaleic anhydride (DMA) to the side amino groups of poly(ethylene glycol)-b-poly(L-lysine) (PEG-b-PLL) and by encapsulating triptolide (TRI) into the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 49 publications
0
32
0
2
Order By: Relevance
“…The following data suggest that single-plaque AGE can also screen for high persistence via screening for negative σ high in magnitude. Experience with non-phage drug delivery vehicles has been that overall persistence is increased by negative σ and decreased by positive σ [32, 33], although some innate immune systems do remove particles with negative σ [34].…”
Section: Discussionmentioning
confidence: 99%
“…The following data suggest that single-plaque AGE can also screen for high persistence via screening for negative σ high in magnitude. Experience with non-phage drug delivery vehicles has been that overall persistence is increased by negative σ and decreased by positive σ [32, 33], although some innate immune systems do remove particles with negative σ [34].…”
Section: Discussionmentioning
confidence: 99%
“…is increased the blood concentration of AMD and half-life of AMD in the plasma. PEG-modi ed nanoparticles, PEG-modi ed grafted polymers, PEG-modi ed polymeric micelles, and PEG-modi ed dendrimers all have been shown to increase the half-life of drugs in blood circulation [43][44][45][46][47]101]. However, several studies also observed that continuous injection of PEG-modi ed nanoparticles could induce immune responses and thus lead to accelerated blood clearance (ABC) [102,103].…”
Section: Blood Circulation After Intravenous Injection Nddssmentioning
confidence: 99%
“…pHresponsive nanocarriers, such as liposomes, nanoparticles, nanogels, polymer-drug conjugates, and micelle, have been designed and reported to have good efficacy and function [127]. Inorganic substances like calcium phosphate, chitosan, closed mesoporous silica nanoparticle pores (MSNPs), and poly(styrene-co-N,N′-dimethylaminoethyl methacrylate nanoparticles (P(St-co-DMAEMA))complexes and mPEG-b-PMaIPG (methoxy-polyethylene glycols (PEG)-bpoly (d-galactopyranose)) nanoparticles have been demonstrated to be sensitive to relatively small pH changes and have good drug release and relatively high antitumor activity [44,49,60,62,63]. Yang et al [61] synthesized the pHsensitive polymer (poly(ethylene glycol)-benzoic iminepoly(gamma-benzyl-l-aspartate)-b-poly(1-vinylimidazole) block copolymer (PPBV) and developed a multistage pHresponsive micelle system for the codelivery of PTX and CUR for the treatment of breast cancer CSCs.…”
Section: Drug Releasementioning
confidence: 99%
“…16,17 The current challenge is to prompt efficient endosomal escape and improve the degradation of nanoparticles in the cytoplasm of cancer cells. 18,19 On the other hand, in view of the pH variation in tumor tissues (pH 6.5-6.9), endo/lysosomes (pH 5.0-5.5) and normal physiological environment (pH 7.4), [20][21][22] pHinduced charge-reversible nanoparticles have been extensively reported to spontaneously improve cellular uptake and controllable drug release through the enhanced permeability and retention effects. 23,24 The negative charge renders nanoparticles with stealth characteristics to avoid non-specific protein binding and prolong retention time.…”
Section: Introductionmentioning
confidence: 99%